Analysis of Simple Additive Weighting (SAW) Methods to Determine The Quality of Student Learning SMK Siti Banun - Dhera; Deci Irmayani; Angga Putra Juledi (Jurnal Mantik, 2021)
It is a daunting challenge to assess the accuracy of student learning quality. Many considerations must be taken into consideration when determining the accuracy of the degree of student learning efficiency. These criteria use to assess students' ability to learn consistently. Since there are so many ways to satisfy this criteria, deciding on the consistency standard of learning scores is problematic. The SAW (Simple Additive Weighting) process solves different parameters of decision-making problems. The SAW method is a multi-criteria decision-making method founded on the idea that the chosen solution must satisfy all criteria. The SAW technique is a multi-criteria decision-making approach based on the optimal option, which would be the nearest to the ideal solution while being the furthest from the negative ideal solution. Calculating the normalization matrix, weighted normalization matrix, comparing the positive and negative ideal solutions, calculating the separation distance for each alternative ideal solution, and calculating the value of each alternative's preference are all steps in the SAW method. The following table displays the results of the SAW process calculation protocol. The information comes from a decision-making framework that distinguishes students who excel in their studies. Bunga Adelia Azahara received a 0.908, while Fadila Dwi Ranti received a 0.932.